2014
DOI: 10.1016/j.vaccine.2013.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of Fluzone® intradermal and high-dose influenza vaccines in older adults ≥65 years of age: A randomized, controlled, phase II trial

Abstract: We conducted a randomized, controlled, multicenter, phase II study to evaluate the immunogenicity and safety of an investigational intradermal (ID) trivalent influenza vaccine (TIV) and a high-dose (HD) intramuscular (IM) TIV in older adults (≥65 years of age). Older adult subjects were immunized with ID vaccine containing either 15μg hemagglutinin (HA)/strain (n=636) or 21μg HA/strain (n=634), with HD IM vaccine containing 60μg HA/strain (n=320), or with standard-dose (SD) IM vaccine (Fluzone(®); 15μg HA/stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 34 publications
3
48
2
7
Order By: Relevance
“…The required 60% of seroprotected volunteers was reached in only some of the studies reporting the results for B strain with values ranging from 66.1 to 100%. Values below 60% were found in the first and second year of Arnou et al 28 (55.7 and 59.9%, respectively) and in Van Damme et al 30 The GMTR was in most instances >2 (range 2.5 and 3.7) except in the second year of Arnou et al, 28 Scheifele et al 31 (1.6) and Tsang et al 60 (1.7) studies. Seroconversion rates >30% were found in 6 trials (range 36.4-46.0%).…”
Section: Immunogenicity Of Fluad and Intanza 15mcg ò In Elderly Peoplmentioning
confidence: 84%
See 2 more Smart Citations
“…The required 60% of seroprotected volunteers was reached in only some of the studies reporting the results for B strain with values ranging from 66.1 to 100%. Values below 60% were found in the first and second year of Arnou et al 28 (55.7 and 59.9%, respectively) and in Van Damme et al 30 The GMTR was in most instances >2 (range 2.5 and 3.7) except in the second year of Arnou et al, 28 Scheifele et al 31 (1.6) and Tsang et al 60 (1.7) studies. Seroconversion rates >30% were found in 6 trials (range 36.4-46.0%).…”
Section: Immunogenicity Of Fluad and Intanza 15mcg ò In Elderly Peoplmentioning
confidence: 84%
“…Table 2 reports HI antibody responses induced following administration of ID vaccine using BD's Soluvia to volunteers aged 60 y in the 9 different clinical studies considered in the present review. [28][29][30][31]41,[57][58][59][60] In the study by Arnou et al 28 the results over 3 consecutive years were reported and in one study 58 ) only the results for A/H3N2 strain were included. The total number of subjects examined was 5035 for A/H3N2 and 5100 for A/H1N1 and B antigens.…”
Section: Immunogenicity Of Fluad and Intanza 15mcg ò In Elderly Peoplmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating these transcriptional profiling data with genotyping information could provide further insights [27]. Additional experiments should also clarify whether alternate formulations of influenza vaccine developed for older adults, such as high-dose or intradermal preparations [28], are able to modify these alterations in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects immunized with ID vaccine were more likely to report more injection-site reactions. 85 An interesting study carried out by Gorse and co-workers assessed the safety and reactogenicity in case of revaccination with ID preparation, performing a phase II, active-controlled, multi-centre, open-label trial in 1,250 adults aged 18-64 years randomly assigned to ID or IM vaccine. Vaccines with ID vaccine reported erythema, induration, swelling, pruritus and ecchymosis more often than those receiving IM vaccine, especially if they had been immunized with ID vaccine in the previous year.…”
Section: Cutaneous Drug and Vaccine Deliverymentioning
confidence: 99%